THE USE OF ANAESTHETIC METHODS IN ATHLETES' ORTHOPEDIC SURGERY: A LITERATURE REVIEW OF THE IMPACT ON REHABILITATION AND QUALITY OF CARE - Zuzanna Kudlińska,; Honorata Juniewicz,; Patryk Heryć,; Karolina Kananowicz,; Ryszard Łagowski,; Julia Kosęda,; Anna Jędrasiak,; Jakub Piotrowski,; Zofia Laska,; Marianna Latour, (International Journal of Innovative Technologies in Social Science, 2025)
Background: Athletes aim for rapid, pain-free return to activity after injury, but many of them require surgery. As the choice of anesthesia for surgery affects postoperative recovery and patient satisfaction it is crucial to analyze which type of anesthesia is adequate. Aim: This literature review was created to analyze the latest information on general versus regional anaesthesia on postoperative rehabilitation, pain management, length of hospital stay, and perceived quality of care in the context of orthopedic procedures in physically active patients.Materials and methods: The review analyzed current literature from Pubmed and other medical databases published between 2000 and 2025. Conclusion: A large number of factors must be taken into account when choosing what type of anaesthesia must be used. Patient collaboration, a holistic approach to the patient and understanding his needs influences the rehabilitation process and thus a faster return to health and physical activity.